Pengaruh Gaya Kepemimpinan,Lingkungan Kerja Dan Worklife Balance Terhadap Turnover Intention Dengan Kepuasan Kerja Sebagai Variabel Mediasi - Nuraeni, Fitri; Wahyu Utomo, Kabul (GEMA EKONOMI, 2023)
Leadership style is important to achieve an effective organizational condition. In addition to leadership style, the environment can also affect individual comfort at work. Work-life balance is also needed to balance work demands. This research uses a quantitative approach. The location of this research was at the SBU Upstream Oil and Gas and Oil and Gas Products at the Service Project of Surveyor Handover and Measurement of Fuel from PT. Pertamina (Persero) to PT. PLN (Persero) and the number of samples obtained by 146 respondents. The instrument used is the Google Form with data analysis using the Partial Least Square (PLS) approach. The conclusion of this study is that job satisfaction has an effect on turnover intention. Meanwhile, leadership style, work environment and work life balance have no effect on turnover intention. For the results of the indirect effect hypothesis test, it is known that only work life balance and job satisfaction have an influence on turnover intention as a mediating variable. Meanwhile, leadership style on job satisfaction and turnover intention as mediating variables do not influence each other. Work environment on job satisfaction on turnover intention as a mediating variable does not have any influence on each other.